The Effect of Religiosity on Adolescent Risky Behaviors - Silvia Mendolia; Alfredo R. Paloyo; Ian Walker (Institute of Labor Economics (IZA), 2018)
We investigate the relationship between religiosity and risky behaviors in adolescence using data from a large and detailed cohort study of 14 year olds who have been followed for seven years. We focus on the effect of the self-reported importance of religion and on the risk of youths having early sexual intercourse, drinking underage, trying cigarettes, trying cannabis, and being involved in fighting at ages 14–17. We use school and individual fixed effects, and we control for a rich set of adolescent, school, and family characteristics, including achievements in standardized test scores at age 11, parental employment, and marital status. We also control for information on personality traits, such as work ethic, self-esteem, and external locus of control. Our results show that individuals with low religiosity are more likely to engage in risky health behaviors, whatever their combination of personality traits. These effects are robust to separate estimations for boys and girls and to the control variables used. Moreover, the results are essentially unchanged when we use Inverse Probability Weighted Regression Adjustment estimation methods – which provide causal estimates conditional on selection on observables only.
Keywords: I10; I12; 330; health behaviors; religiosity; personality; fixed effects